Pelatihan Pembuatan Pembalut Kain di Desa Proto Barat, Kecamatan Kedungwuni, Kabupaten Pekalongan - Dwi Bagus Pambudi; Mahdanya Puteri; Indah Aulia; Khoerurrohim Khoerurrohim; Imroatul Maghfiroh; Gigih Setianto (LPPM Akbid Harapan Ibu Pekalongan, 2023)
Cloth pads are a necessity during menstruation. According to research, disposable sanitary napkins currently in use are carcinogenic and contain harmful substances that have the potential to cause dangerous diseases for the reproductive organs. This training aims to find out how to manufacture, use and advantages of eco-friendly cloth sanitary napkins. These innovative cloth pads are made of fleece, diadora, cotton, waterproof, thread, sewing needle, ruler, scissors, pencil/ballpoint pen/marker, and adhesive. The method used with several steps, such as the presentation of material on how to make cloth pads and the advantages and disadvantages of cloth pads, product making begins with pattern making to the sewing stage, and the conclusion of the activity. The result is a product in the form of eco-friendly cloth pads.